The role of Energy Conservation Building Code 2017 in Indian Energy Policy - Ali, Shaikh Shamser; Tyagi, Dr Ruchi (International journal of recent technology and engineering, 2020)
With the advancement in technology and the need for development by both developed and developing countries, energy plays a vital role in the whole process of sustainability. India’s security score has been declining since 2000 due to decrease in energy storing capacity, scarcity in primary energy supply sources and to much dependency on import. The World Energy Council’s latest Energy Trilemma Index covering 128 countries shows how energy policies are changing around the world. India’s energy policies and infrastructure are rated among the worst in the world with 109th rank with overall score of 50.3. India scores high on Energy Security but struggles on sustainability and equity indicators giving clear indication on revisiting ECBC 2017. This paper reviews and compares ECMs between two versions of the code titled ECBC 2007 and ECBC 2017 and identify the role of human behavior as a missing link. This paper suggest Low Cost Energy Conservation Measure focused on sustainability and environment.